2021
DOI: 10.3390/nu13082750
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Glucosinolates by Gut Microbiota

Abstract: Glucosinolates (GLS) and their derivatives are secondary plant metabolites abundant in Brassicaceae. Due to the enzymatic reaction between GLS and myrosinase enzyme, characteristic compounds with a pungent taste are formed, used by plants to defend themselves against insect herbivores. These GLS derivatives have an important impact on human health, including anti-inflammation and anti-cancer effects. However, GLS derivatives’ formation needs previous enzymatic reactions catalyzed by myrosinase enzyme. Many of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 95 publications
1
37
0
Order By: Relevance
“…In the chrysomelid Psylliodes chrysocephala , gut microbiota seem to be involved in isothiocyanate detoxification, because when they were suppressed, adults showed about 11-fold higher levels of isothiocyanates than the control group 44 . Likewise, the gut microbiome in humans and other vertebrates contributes to the production of isothiocyanates and nitriles in the absence of plant myrosinase activity 45 48 . In P. cochleariae, next to microbiota also a gregarine species occurs in the gut 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In the chrysomelid Psylliodes chrysocephala , gut microbiota seem to be involved in isothiocyanate detoxification, because when they were suppressed, adults showed about 11-fold higher levels of isothiocyanates than the control group 44 . Likewise, the gut microbiome in humans and other vertebrates contributes to the production of isothiocyanates and nitriles in the absence of plant myrosinase activity 45 48 . In P. cochleariae, next to microbiota also a gregarine species occurs in the gut 49 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that plant myrosinases are not necessarily involved in the detoxification mechanism. Gut microbiota may play a role in the formation of isothiocyanates, nitriles, and amines independent of plant myrosinases, as known for humans, other vertebrates, and insects (Mutlib et al, 2002;Angelino et al, 2015;Welte et al, 2016a, b;Liu et al, 2017;Liou et al, 2020;Sikorska-Zimny and Beneduce, 2021) and also suggested for P. cochleariae (Friedrichs et al, 2020(Friedrichs et al, , 2022.…”
Section: Detoxification Of the Brassicaceae Defence Metabolitesmentioning
confidence: 92%
“…Quite varied responses of human commensal microbiota to dietary brassica have been found among hosts, which suggests that the host species/environment, and the basal microbiota structure may affect results. In clinical studies, highly variable conversion rates of GSLs to ITCs have been reported, ranging from 1% to 40%, following identical oral administration of a broccoli sprouts extract [ 36 ], suggesting that prior individual differences in gut microbial communities lead to variation in GSL bioactivation rates [ 9 , 11 ].…”
Section: Metabolism Of Glucosinolates and Resulting Itc Bioavailabili...mentioning
confidence: 99%
“…Over the past several decades, a large number of studies focusing on physiological effects of brassica GSLs have been reported, with findings of ITCs’ activities in anti-inflammation, chemoprotection, neuroprotection, anti-obesity, and modulation of gut microbiota, both in clinical studies and in animal/cell culture models [ 3 , 7 , 8 ]. As a result of rapid development in metagenomic sequencing techniques, the impact of brassica consumption on host microbiota has begun to unfold [ 9 , 10 , 11 ]. However, in clinical studies, despite numerous animal and cell culture studies suggesting the physiological benefits of brassica and their ITCs, there remains substantial interindividual variation in the extent of conversion of GSL to ITC—and thus in the resulting absorption and bioactivity of ITCs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%